Social support and self-esteem in people with physical disabilities - Lestari, Rini; Fajar, Maharani (Indigenous, 2020)
Abstract. Self-esteem is an important individual factor because it determines personality and influences human health. One factor affects self-esteem is social support. The purpose was to examine the relationship between social support and self-esteem, and the contribution of form of social support for self-esteem in people with physical disabilities. The hypothesis was there was a positive relationship between social support and self-esteem in people with physical disabilities. This was a quantitative research that involved social support and self-esteem. The subject  was 103 people with physical or innate disabilities (accidents, illness),  18 -35 years old and participate in social rehabilitation programs. The instruments were social support scale (SDS) and self-esteem scale (SHD). Data analysis technique was regression analysis. The result was social support has  positive relationship with self-esteem in people with physical disabilities. Social support contributed amount 47.4% for self-esteem. Contribution of instrumental support to self esteem was the highest among emotional support, information, and appreciation. The instrumental support was the highest contribution because it was currently more needed by people with physical disabilities who were adults to work and earn a living. People with physical disabilities had medium social support and self-esteem.  Keywords: social support, self-esteem, people with physical disabilities  Abstrak. Harga diri  menjadi faktor individu yang sangat penting karena menentukan kepribadian dan mempengaruhi kesehatan manusia. Tujuan penelitian ini untuk menguji hubungan antara dukungan social dengan harga diri dan kontribusi  bentuk-bentuk dukungan sosial pada penyandang disabilitas fisik. Adapun hipotesis penelitian ini adalah terdapat hubungan positif antara dukungan sosial dengan harga diri pada penyandang disabilitas fisik. Penelitian ini merupakaan penelitian kuantitatif yang melibatkan variable dukungan social sebagai independen variable dan harga diri sebagai dependen variable. Subjek penelitian ini adalah 103 penyandang disabilitas fisik bawaan atau non bawaan (kecelakaan, penyakit), 18 -35 tahun dan mengikuti program rehabilitasi sosial.  Skala dukungan social (SDS) digunakan untuk mengukur dukungan sosial dan skala harga diri (SHD) untuk mengukur harga diri. Teknik analisis regresi digunakan untuk menguji hipotesis yang diajukan peneliti. Hasil analisis menunjukkan dukungan social memiliki hubungan positif yang sangat signifikan dengan harga diri pada penyandang disabilitas fisik. Dukungan sosial berperan terhadap harga diri dengan memberikan kontribusi sebesar  47.4%. Kontribusi dukungan instrumental terhadap harga diri tertinggi dibandingkan dukungan emosional, informasi dan penghargaan. Dukungan instrumental paling tinggi karena dukungan instrumental saat ini lebih dibutuhkan oleh penyandang disabilitas fisik yang berusia dewasa untuk bekal bekerja dan mencari nafkah. Dukungan social dan harga diri penyandang disabilitas termasuk dalam kategori sedang. Kata kunci     : dukungan social, harga diri, penyandang disabilitas fisik